Analisis Penerapan Sistem Manajemen Kesehatan dan Keselamatan Kerja (SMK3) dalam Penggunaan Alat Pelindung Diri (APD) di CV. Sarana Sejahtera Teknik - Dwi Kurnia Akbar; Asep Erik Nugraha; Hamdani Hamdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Developments in the industrial world have given rise to better tools and technology. However, the production equipment results in potential hazards that will cause losses if not controlled. CV. Sarana Sejahtera Teknik is a company engaged in the fabrication of dice racks, special fallets, fallet boxes, push trolleys, conveyors, shutter conveyors, stainless boxes, stainless steel piping, loading doc containers, and steel meanings. During the work process, many of the workers did not apply K3 properly such as not using gloves, shoes, and other personal protective equipment. The purpose of this study was to measure the performance of occupational safety and health, especially in the discipline of using work safety equipment. The method used is the OHS Management System (SMK3) approach. The results obtained show that there are still many workers who do not use PPE when doing work. Controls that can be carried out are in the form of establishing HSE policies to be more assertive, such as the existence of SOPs, socialization and education, to supervision related to the implementation of HSE that has been planned.